1983
DOI: 10.1017/s0022112083000440
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of fully developed turbulent flows in ducts of arbitrary cross-section

Abstract: The algebraic stress model developed by Launder & Ying for the secondary flow of the second kind was employed with the κ and ε model for the prediction of fully developed turbulent flows in square, rectangular and trapezoidal ducts using the numerical procedure designed for ducts of arbitrary cross-sectional shape. Results of the calculation are compared extensively with available experimental data, with strong emphasis on the local structures of turbulence to reveal full features of this particular stress mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…The present prediction (NR model) compares quite well with the data. The predictions by Nakayama et a1 [12], which is characteristic of those based on the LY model show magnitudes which are a t least an order of magnitude too low. This observation has, of course, been widely discussed in the literature without isolating the true cause.…”
Section: Trapezoidal Ductmentioning
confidence: 85%
“…The present prediction (NR model) compares quite well with the data. The predictions by Nakayama et a1 [12], which is characteristic of those based on the LY model show magnitudes which are a t least an order of magnitude too low. This observation has, of course, been widely discussed in the literature without isolating the true cause.…”
Section: Trapezoidal Ductmentioning
confidence: 85%
“…Recently, Qin and Fletcher [1] showed that Prandtl's secondary flow of the second kind has a significant effect in the transport of heat and momentum, as revealed by the recent Large Eddy Simulation (LES) technique. Several experimental and numerical studies have been conducted on turbulent flow though of non-circular ducts: Nikuradse [2]; Gessner and Emery [3]; Gessner and Po [4]; Melling and Whitelaw [5]; Nakayama et al [6]; Myon and Kobayashi [7]; Assato [8]; Assato and De Lemos [9]; Home et al [10]; Luo et al [11]; Ergin et al [12] Launder and Ying [13]; Emery et al [14]; Hirota et al [15]; Rokni [16]; Hongxing [17]; Yang and Hwang [18]; Park [19];Zhang et al [20]; Zheng et al [21]; Su and Da Silva Neto [22]; Saidi and Sundén [23]; Rokni [24]; Valencia [25]; Sharatchandra and Rhode [26]; Campo et al [27]; Rokni and Sundén [28]; Yang and Ebadian [29] and others. The Melling and Whitelaw´s [5] experimental work shows characteristics of turbulent flow in a rectangular duct where they have been used a laser-Doppler anemometer in which report the axial development mean velocity, secondary mean velocity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Melling and Whitelaw´s [5] experimental work shows characteristics of turbulent flow in a rectangular duct where they have been used a laser-Doppler anemometer in which report the axial development mean velocity, secondary mean velocity, etc. Nakayama et al [6] show the analysis of the fully developed flow field in rectangular and trapezoidal cross-section ducts; finite difference method was implemented and the model of Launder and Ying [13] has been used. On the other hand, Hirota et al [15] present an experimental work in turbulent heat transfer in square ducts; they show details of turbulent flows and temperature fields.…”
Section: Introductionmentioning
confidence: 99%
“…Such secondary flows not only cause a reduction in the volumetric flow rate, but they can also cause the axial velocity field to be distorted with an outward shift of the contours of constant velocity. In addition, it is well known that the turbulent flow in straight noncircular ducts is characterized by the occurrence of secondary flows (see Jones 1965 andNakayama et al, 1983). A clear understanding of the evolution and consequences of the turbulent secondary flows in curved and straight ducts is, therefore, quite important from the design standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…The case of fully-developed turbulent flow in straight ducts of square cross section was studied by Gessner and Jones (1965), Melling and Whitelaw (1976), and Nakayama, et al (1983), among others. Gessner and Jones (1965) conducted a series of experiments using hotwire anemometry to analyze fully-developed turbulent flow in a square duct at a Reynolds number of 150,000.…”
Section: Introductionmentioning
confidence: 99%